2015
DOI: 10.1155/2015/906039
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of a Selective Kappa-Opioid Receptor Agonist, U50488, in Guinea Pig Heart Tissues

Abstract: The differential effects of a selective kappa- (κ-) opioid receptor agonist, U50488, were elucidated by monitoring the contraction of isolated guinea pig atrial and ventricular muscles. In electrically driven left atria, U50488 in nanomolar concentration range decreased the contractile force. Norbinaltorphimine (norBNI), a selective κ-receptor antagonist, and pertussis toxin (PTX) abolished the negative inotropic effect of U50488. In contrast, the inhibitory effect was not affected by the pretreatment of atrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
0
2
1
Order By: Relevance
“…Although our results indicate that κ receptor agonist actions are selective and can be blocked by its specific antagonists (Hung et al, 2015;Vonvoigtlander et al, 1983), the endogenous opiates like endomorphin-1 and dynorphin-B inhibit the response to acetylcholine (ACh) in IHC of the rat, probably acting directly in ACh A Kruskal-Wallis test showed that the concentration of U-50488 significantly affected the current amplitude (H = 24.6, P = 0.00012, df = 3), followed by the Tukey's test, demonstrated that all the groups were different from the control (P = 0.03, 0.0004, 0.00005, respectively); within groups, there was a tendency but no significant difference. Inhibitory action of U-50488 is already significant at concentrations as low as 10 nM (P < 0.05).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Although our results indicate that κ receptor agonist actions are selective and can be blocked by its specific antagonists (Hung et al, 2015;Vonvoigtlander et al, 1983), the endogenous opiates like endomorphin-1 and dynorphin-B inhibit the response to acetylcholine (ACh) in IHC of the rat, probably acting directly in ACh A Kruskal-Wallis test showed that the concentration of U-50488 significantly affected the current amplitude (H = 24.6, P = 0.00012, df = 3), followed by the Tukey's test, demonstrated that all the groups were different from the control (P = 0.03, 0.0004, 0.00005, respectively); within groups, there was a tendency but no significant difference. Inhibitory action of U-50488 is already significant at concentrations as low as 10 nM (P < 0.05).…”
Section: Discussioncontrasting
confidence: 59%
“…Although our results indicate that κ receptor agonist actions are selective and can be blocked by its specific antagonists (Hung et al, 2015; Vonvoigtlander et al, 1983), the endogenous opiates like endomorphin‐1 and dynorphin‐B inhibit the response to acetylcholine (ACh) in IHC of the rat, probably acting directly in ACh receptors (Lioudyno et al, 2002). The κ receptor agonists U‐50488 and pentazocine used at large concentrations (≅100 mM) may significantly modify the auditory nerve compound action potential.…”
Section: Discussionmentioning
confidence: 85%
“…Exogenous and endogenous opioids exhibit pharmacological effects via interacting with G-protein-coupled opioid receptor system, encompassing δ-, κ-, and µ-opioid receptors. 57,58 All the subtypes of opioid receptors are widely distributed in the atria and the ventricles of the heart for initiating a cascade of events involved in cardioprotection against sustained ischemia–reperfusion injury. 59,60 The heart is a complex neuroendocrine organ that synthesizes endogenous opioids in the heart that may act in autocrine or paracrine fashion to modulate functioning of the heart.…”
Section: Discussionmentioning
confidence: 99%